Community empowerment in nutrition improvement with nutrient-dense food creations based on local food in Gresik Regency - Dwi Novri Supriatiningrum; Inayatul Ilahiyah; Alfiyatus Salimah (Community Empowerment, 2022)
An In Gresik Regency, it was found that 132 toddlers were malnourished, 55 boys and 77 girls. From the results of weighing children under five at the Posyandu in Petiken Village until January 2020, the prevalence of undernourished children under five was 8.30%, while the prevalence of undernourished children was 1.06%. Through community service activities with counseling methods and the practice of making food made from local food with practical processing and producing nutrient-dense products for toddlers, school-aged children, and adolescents. The results of this activity are nutritional status assessments, waist circumference measurements, and blood pressure checks. Some of the participants belonged to the category of obesity, and optimal blood pressure. Thus, the people of Petiken Village are recommended to use local food ingredients for healthy snacks and routinely utilize health services in the surrounding area in an effort to anticipate degenerative diseases.